RANCANG BANGUN ALAT PEMILIN TAMPAR PELEPAH PISANG DESA KADUNGREJO KECAMATAN BAURENO KABUPATEN BOJONEGORO - Mundari, Siti; Yuliaty, Erma; Arief, Zainal (Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2014)
Kadungrejo village situated on the banks of the Solo River. This village is a village predominantly fertile rice growing are effective only harvest once a year because the flooded Bengawan Solo almost certainly occur every year. Majority of the population live on less prosperous regions. While the non-rice crops that are often found in yards and houses along the banks of the Solo River are banana plants. Banana plants are very many benefits. In addition to fruit and leaves are also the sheath.During this banana thrown away because they are not any good or just a waste. New 10 years ago because of the demand of stem of the banana bunch, the villagers Kadungrejo banana processing into economically valuable goods which are sold for sale. Villagers Kadungrejo very grateful because it can be used to make a living. During this time the problem occurs is the inability of the population to be able to meet the demand of collectors slap.The inability of the population to be able to meet the demand because they do slap on the sidelines of time and equipment to wring so simple that it takes a long time. Average population can only produce less than 10 kg slap in 1 day. Though slap banana production process is not too complicated. With the use of existing tools, slap the resulting average diameter no less so in accordance with the request that resulted in a low slap appreciated. Besides, existing tools make tired quickly so that the results obtained little slap and slap on the side of making less can be optimized.Kata Kunci: Pelepah pisang, alat pemilin